1991
DOI: 10.1182/blood.v77.8.1691.bloodjournal7781691
|View full text |Cite
|
Sign up to set email alerts
|

Hemonectin mediates adhesion of engrafted murine progenitors to a clonal bone marrow stromal cell line from Sl/Sld mice

Abstract: Mutant Sl/Sld mice exhibit decreased marrow hematopoiesis. The defect is known to reside in the marrow microenvironment of these animals, which is reproduced in vitro by primary marrow explants as well as by cloned marrow stromal cell lines. Bone marrow progenitor cells are incapable of adhering to primary Sl/Sld stromal cells or cloned stromal cell lines derived from them to form cobblestone-islands and proliferate. The role of hemonectin, a marrow-specific adhesion protein in the defective hematopoiesis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…In the latter study, hemonectin was found to be a lineage-specific adhesion molecule for granulocyte lineage cells. In a similar study, Anklesaria et al found that the adhesion of haematopoietic progenitor cells to the stromal cells was mediated and inhibited by hemonectin and antihemonectin, respectively (Anklesaria et al, 1991).…”
Section: Extracellular Matrix Components and Other Factorsmentioning
confidence: 87%
See 1 more Smart Citation
“…In the latter study, hemonectin was found to be a lineage-specific adhesion molecule for granulocyte lineage cells. In a similar study, Anklesaria et al found that the adhesion of haematopoietic progenitor cells to the stromal cells was mediated and inhibited by hemonectin and antihemonectin, respectively (Anklesaria et al, 1991).…”
Section: Extracellular Matrix Components and Other Factorsmentioning
confidence: 87%
“…Hemonectin, which is a BM-specific adhesion protein (Anklesaria et al, 1991), has been also reported to be expressed by BM endothelial cells (Bradstock and Gottlieb, 1995), and is found in BM stem cell niche (Campbell et al, 1987). It was shown that the loss of binding to hemonectin may lead to egress of mature granulocytes from BM (Campbell et al, 1987).…”
Section: Extracellular Matrix Components and Other Factorsmentioning
confidence: 99%